Membrane-based separations in metallurgy principles and applications - Jiang, Lan Ying; Li, Na (Amsterdam Elsevier, 2017)
Membrane-Based Separation in Metallurgy: Principles and Applications begins with basic coverage of the basic principles of the topic and then explains how membrane technology helps in the development of new environmentally friendly and sustainable metallurgical processes.
The book features the principles of metallurgical process and how widely the membrane-based technology has been applied in metallurgical industry, including the basic principles of membrane-based separation in terms of material science, membrane structure engineering, transport mechanisms, and module design, detailed metallurgical process flowcharts with emphasis on membrane separations, current process designs, and describes problems and provides possible solutions. In addition, the book includes specific membrane applications, molecular design of materials, fine tuning of membrane’s multi-scale structure, module selection and process design, along with a final analysis of the environmental and economic benefits achieved by using these new processes.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Metallurgy; Separation (Technology).; Electrometallurgy; Electronic books